2023
DOI: 10.1029/2022ef003268
|View full text |Cite
|
Sign up to set email alerts
|

Projected Impact of Increased Global Warming on Heat Stress and Exposed Population Over Africa

Abstract: During the last decades, most of African countries have experienced a trend of warming, which has been increasing at rates higher than the global average rate of temperature increase (Colin, 2011). According to the Intergovernmental Panel on Climate Change's report (IPCC, 2022), climate change risks will rapidly increase in the mid-to-long term with continued global warming, particularly in areas already exposed to high temperatures. Furthermore, projections also suggest that by 2050, half of the net increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…In such conditions, normal rainfall is likely interpreted as an extreme event as it can lead to flooding. NTX35 is expected to increase together with NTN25, meaning a possible risk of thermal discomfort (Fotso‐Nguemo et al, 2022, 2023) and therefore heat‐related illness. The use of air conditioners to equip homes or workplaces is the most widely used means of adaptation.…”
Section: Possible Implications For Socio‐economic Sectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such conditions, normal rainfall is likely interpreted as an extreme event as it can lead to flooding. NTX35 is expected to increase together with NTN25, meaning a possible risk of thermal discomfort (Fotso‐Nguemo et al, 2022, 2023) and therefore heat‐related illness. The use of air conditioners to equip homes or workplaces is the most widely used means of adaptation.…”
Section: Possible Implications For Socio‐economic Sectorsmentioning
confidence: 99%
“…In addition, the number and duration of hot nights are expected to increase over equatorial Africa, together with the intensification of the frequency of heat wave events, and may amplify with increasing global warming levels (Weber et al, 2018). Recent studies by Fotso‐Nguemo et al (2022, 2023) reveals that as the world warms up, the population of Central Africa would be exposed to the risk of discomfort related to heat stress, which would increase with the level of warming.…”
Section: Introductionmentioning
confidence: 99%
“…Although our study focuses on population exposure to record-breaking extreme events and our results cannot be compared directly to previous work performed at the global or regional scales, the population exposure hotspots identified in this study mostly correspond to areas with high population exposure to extreme events, such as CAF, SAS, and EAS in previous studies (Fotso-Nguemo et al, 2023;Iyakaremye et al, 2021;Kumar & Mishra, 2020;W. Zhang & Zhou, 2020;Zhao et al, 2021).…”
Section: Main Findings and Significancementioning
confidence: 72%
“…Park & Jeong, 2022; C. Yin et al., 2022) and precipitation or fluvial flooding (Alfieri et al., 2017; H. Chen & Sun, 2021; Hirabayashi et al., 2013; Yamazaki et al., 2018) under different scenarios based on general circulation model (GCM) simulations (mainly Coupled Model Intercomparison Project Phase 6 [CMIP6] data) at the global scale. Moreover, regional‐scale studies have been carried out in areas with high vulnerability and dense populations such as South Asia (SAS) (Kumar & Mishra, 2020; Zhao et al., 2021), East Asia (EAS) (W. Zhang & Zhou, 2020), North America (Jones et al., 2015; Swain et al., 2020), and Africa (Fotso‐Nguemo et al., 2023; Iyakaremye et al., 2021). Considering that isolated studies of individual hazards performed through climate risk assessment may underestimate the amplifying effects of multiple extreme event combinations, some studies have been conducted to explore population exposure to compound events (AghaKouchak et al., 2020; Das et al., 2022; Raymond et al., 2020; Ridder et al., 2022; Wang et al., 2020; J. Yin et al., 2023; G. Zhang et al., 2022; Zscheischler et al., 2018), suggesting that under the impact of climate change, increasing numbers of people will be affected by different climate extremes, even compound events.…”
Section: Introductionmentioning
confidence: 99%
“…They also highlighted that future exposure to dangerous heat will be determined mainly by demographic changes alone or by combined climate and population changes, although the diversity of projected results could be attributed to the uncertainty in climate model simulations and population modelling approaches. In the same vein, using both RCP2.6 and RCP8.5 scenarios, Fotso‐Nguemo et al (2023) found that by the end of the 21st century, global warming is expected to lead to a substantial increase in the area extent affected by heat stress across Africa, underlining the need for urgent adaptation and mitigation policies for countries.…”
Section: Introductionmentioning
confidence: 98%